Exploratory Component Analysis of Entrepreneurial Adaptation Factors towards Business Survival in the Covid-19 Pandemic Crisis - Suybangdum, Panumas; bunnoon, patcharin; Tuncharo, Supasuta (Journal of Humanities and Social Sciences Thonburi University, 2022)
Objectives of this research were 1) to study the factors of entrepreneurial adaptation towards business survival and 2) to analyze the exploratory component of the factors of entrepreneurial adaptation to their operations business to survive by using questionnaires to collect data The sample group consisted of 1180 people. The statistics used were percentage, mean, standard deviation. and exploratory component analysis The results of the research were as follows: 1) the overall adjustment of entrepreneurs towards business survival at a high level; 2) an analysis of the factors of entrepreneurs' adjustment towards Operations for the survival of the business found that there were 2 factors as follows: 1) New normal management consisted of 15 variables and 2) confidence in quality with 1 variable